Implementasi Penataan Ruang Terbuka Hijau Pada Taman di Kota Magelang Berdasarkan Perda Nomor 1 Tahun 2014 Tentang Penataan Ruang Terbuka Hijau - Puspasari, Rina Sulistya; Purnaweni, Hartuti; Rengga, Aloysius (Journal of Public Policy and Management Review, 2015)
With the new city branding of Magelang as â€œA City of Million Flowersâ€, the Local Goverment of Magelang tries to beautify the landscape and appearance of the city through the arrangement of the parks in Magelang City. The long term purpose of the city branding program is increasing the ratio of Open Green Space to make Magelang a beautiful ecocity. Another purpose of the park arrangement program is to fulfill the mandate in Law Number 26 Year 2007 about Spatial Planning that open green space area minimum has to be 30%. Magelang Municipal Goverment formed Local Regulation Number 1 Year 2014 about Open Green Space Planning to support the open green space arrangement of park in Magelang City. The purpose of this study is to analyse and describe the implementation of open green space arrangement in Magelang city park according to Local Regulatin Number 1 Year 2014 about Open Green Space Planning. This reseach is qualitative â€“ descriptive. The result of this reasearch shows that the implementation of Open Green Space Planning of the park in Magelang City consist of planning, utilizing and controling. There are factors that hamper the implementation, the factors are the limited space of Magelang City, the lack of support and participation from the society shown from many action of thief, park destruction, and vandalism. Proposed recommendation to the Magelang Municipal Goverment is to increase the society participation by providing place in which the society can express their aspiration from discussion forum, mass media, or Website that could be accessed by society, as well as forming an exclusive group that supports of city branding program of â€œA City of Million Flowersâ€ .